Validity of simple field tests as indicators of elite female field hockey match performance - Sparks, M.; Powell, C.; Pienaar, C. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND Due to the change in field hockey match format, the need exits for research to determine whether current fitness test are still valid indicators of match performance. This study aimed to determine the direct validity of the 5-m multistage shuttle test (5-m MST) and Yo-Yo Intermittent recovery level 1 test (Yo-Yo IR1) by correlating their results with external load measures in international field hockey matches.